Implementation of Online Veterinary Hospital on Cloud Platform. - Chen, Tzer-Shyong; Chen, Tzer-Long; Chung, Yu-Fang; Huang, Yao-Min; Chen, Tao-Chieh; Wang, Huihui; Wei, Wei (Journal of Medical Systems, 2016)
Pet markets involve in great commercial possibilities, which boost thriving development of veterinary hospital businesses. The service tends to intensive competition and diversified channel environment. Information technology is integrated for developing the veterinary hospital cloud service platform. The platform contains not only pet medical services but veterinary hospital management and services. In the study, QR Code andcloud technology are applied to establish the veterinary hospital cloud service platform for pet search by labeling a pet's identification with QR Code. This technology can break the restriction on veterinary hospital inspection in different areas and allows veterinary hospitals receiving the medical records and information through the exclusive QR Code for more effective inspection. As an interactive platform, the veterinary hospital cloud service platform allows pet owners gaining the knowledge of pet diseases and healthcare. Moreover, pet owners can enquire and communicate with veterinarians through the platform. Also, veterinary hospitals can periodically send reminders of relevant points and introduce exclusive marketing information with the platform for promoting the service items and establishing individualized marketing. Consequently, veterinary hospitals can increase the profits by information share and create the best solution in such a competitive veterinary market with industry alliance.